Respuesta :

Answer:

[tex]f(x)=5\cdot 2^x + 8[/tex]

Step-by-step explanation:

To find the equation for the exponential function passing through the points (1, 18) and (3, 48), and with an asymptote at y = 8, we can use the general form of an exponential function:

[tex]\boxed{\begin{array}{l}\underline{\textsf{General form of an Exponential Function}}\\\\ y=ab^x+c \\\\\textsf{where:}\\\phantom{ww}\bullet\;\textsf{$a$ is the initial value ($y$-intercept).}\\ \phantom{ww}\bullet\;\textsf{$b$ is the base (growth/decay factor) in decimal form.}\\\phantom{ww}\bullet\;\textsf{$y=c$ is the horizontal asymptote.}\\ \end{array}}[/tex]

In this case the horizontal asymptote is y = 8, so c = 8:

[tex]y = ab^x + 8[/tex]

Substitute the given points into the equation to form two equations:

[tex]\underline{\textsf{Equation 1}}\\\\ab^1+8=18\\\\ab=10[/tex]

[tex]\underline{\textsf{Equation 2}}\\\\ab^3+8=48\\\\ab^3=40[/tex]

Divide the second equation by the first equation to eliminate a, then solve for b:

[tex]\dfrac{ab^3}{ab}=\dfrac{40}{10}\\\\\\b^2=4\\\\\\\sqrt{b^2}=\sqrt{4}\\\\\\b=2[/tex]

We always take the positive square root of b because when the base of an exponential function is negative, the function can result in complex values, leading to non-real solutions. As a consequence, an exponential function with a negative base does not have the ability to exhibit consistent growth or decay.

Now, substitute b = 2 into the equation ab = 10 and solve for a:

[tex]a( 2)=10\\\\\\a=\dfrac{10}{ 2}\\\\\\a= 5[/tex]

Substitute the values of a, b, and c back into the exponential function:

[tex]y=5\cdot 2^x + 8[/tex]

Therefore, the exponential function that passes through the points (1, 18) and (3, 48) and has an asymptote of y = 8 is:

[tex]\Large\boxed{\boxed{f(x)=5\cdot 2^x + 8}}[/tex]

Ver imagen semsee45
ACCESS MORE